The Study of Individual Morality and Internal Control and the Relationship on Accounting Fraud - M Muttiarni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Good governance is required by society to create a government free of corruption, collusion, and nepotism. According to this study, individual morality and internal control impact accounting trends in Makassar City Regional Work Units. This study's data was obtained directly from the source without the use of intermediaries, namely by taking the data to the Makassar City Regional Revenue agency office and processing it using a Direct Questionnaire with 43 respondents as research objects. Hypothesis testing using the data analysis technique used, multiple linear regression with the Statistical Package for Social Science, was used for the analysis method (SPSS). According to hypothesis testing results, individual Morality and Internal Control have a negative and significant effect on the Tendency of Fraud Accounting. The study's findings are expected to lead to a greater focus on individual morality and internal control systems to reduce accounting fraud.